Does cultural heritage monetary value have an impact on visits? An assessment using official Italian data. Issue 3 (May 2018) - Guccio, Calogero; Lisi, Domenico; Mignosa, Anna; Rizzo, Ilde
In this article, we try to investigate which factors affect the visits to cultural heritage (CH), using Italy as a case study. We adopt a broad definition of CH including archaeological and historical sites, historical buildings and museums, focusing our attention on State CH. In our empirical analysis, we use a rather innovative indicator of CH value, that is, the monetary value of State CH, officially provided by the Ministry of Economy and Finance. Using these data, this article aims at evaluating if such monetary value has a significant role in stimulating visits to cultural sites for the years 1996–2010. We also control for other factors potentially affecting the number of visits to cultural sites, such as alternative tourist attractors and the regional performance in the tourism sector. To the best of our knowledge, this is the first study that attempts to investigate the effect of CH monetary value on cultural participation.